2020
DOI: 10.1021/acsaem.0c00501
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Carbon Dots-Matrix Structures: An Efficient Strategy for High-Performance Electric Double Layer Capacitors

Abstract: As a type of nanomaterials that has received much attention, carbon dots (CDs) have played distinctive roles in various energy storage materials, benefiting from their advantages of controllable surface structures, good solubility, stable chemical properties, and low cost. However, noncontinuous structures of CDs will hinder their further application due to their unsatisfactory charge transfer performance. Here, we develop a series of carbon materials with CDs-carbon matrix structure based on mixed biogels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…With the CDs fused into the carbon skeleton, the surface roughness was increased, thus achieving a high surface area, which led to the higher capacity. 32,33 CDs were also applied as the electrodes for batteries and achieved better cycle ability and higher capacity due to the special carbon frame structure with a larger interlayer space and a large surface area. 34 In this work, we applied N-doped CDs and mixed with lignin-based ACs under an optimized ratio, making the CDs fully and uniformly distributed on the surface of the highly porous AC matrix to form a three-dimensional (3D) carbon composite with an interior surface decorated with CDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the CDs fused into the carbon skeleton, the surface roughness was increased, thus achieving a high surface area, which led to the higher capacity. 32,33 CDs were also applied as the electrodes for batteries and achieved better cycle ability and higher capacity due to the special carbon frame structure with a larger interlayer space and a large surface area. 34 In this work, we applied N-doped CDs and mixed with lignin-based ACs under an optimized ratio, making the CDs fully and uniformly distributed on the surface of the highly porous AC matrix to form a three-dimensional (3D) carbon composite with an interior surface decorated with CDs.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have tried to integrate CDs into the porous carbon frameworks by the one-step calcination-activation method and employed them as the EDLC materials. With the CDs fused into the carbon skeleton, the surface roughness was increased, thus achieving a high surface area, which led to the higher capacity. , CDs were also applied as the electrodes for batteries and achieved better cycle ability and higher capacity due to the special carbon frame structure with a larger interlayer space and a large surface area …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that CDs can be used to detect Cr(VI) optically [11,12]. However, some issues remain in sensor probe application, such as CD agglomeration with increasing detection and storage time [13]. One possible solution to overcome this problem is to graft with other materials, such as CN [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a new class of carbon nanomaterial, carbon quantum dots (CQDs) have received widespread attention in SCs owing to their tunable redox activity, rich surface functional groups, high water dispersion, low production cost, and extensive raw materials . Until now, CQDs have been mainly used as an additive or a structure-directing agent for constructing advanced CQD-based nanocomposites, such as CQDs/metal oxides, CQDs/metal sulfides, CQDs/polymers, , CQDs/metal hydroxide, , and CQDs/activated carbon. , As electrode materials for SCs, these nanocomposites showed excellent capacitance performance. It has been found that CQDs can minimize charge transfer or internal resistance, accelerate ion transportation, and reduce the volume expansion effect of metal oxides as well as provide additional active sites and improve surface hydrophilicity for conductive polymers and activated carbon, which will be conducive to the improvement oin capacitive performance.…”
Section: Introductionmentioning
confidence: 99%